I have a problem:

ux^a=x

The solution shows:

ux^a=x;x^a-1=1/u;x=(1/u)^1/(a-1)

I understand everything except how they got the a-1 exponent on x in the first step. Could someone help me understand better?

Thanks!

Printable View

- Jan 28th 2009, 05:52 PMatillman34817Help understanding solution to problem involving roots
I have a problem:

ux^a=x

The solution shows:

ux^a=x;x^a-1=1/u;x=(1/u)^1/(a-1)

I understand everything except how they got the a-1 exponent on x in the first step. Could someone help me understand better?

Thanks! - Jan 28th 2009, 05:56 PMatillman34817I think I figured it out
The a-1 exponent comes from divind both sides by x and then simplifying using the division exponent rule x^a/x = x^a-1

Is that right?